Russian-Egyptian Cooperation in the Context of the Prospects for the Great Eurasian Partnership - O. N. Misko; A. Sh. Darwish (Евразийская интеграция: экономика, право, политика, 2023)
The article examines the development of economic cooperation and trade exchange between Russia and Egypt over the past ten years. The most important joint projects of Russia and Egypt at the level of the public and private sectors, as well as the most important obstacles to expanding the scope of economic cooperation and trade exchange at the private sector level between the Egyptian and Russian parties are analyzed.Aim. This study aims to monitor the various forms of economic cooperation between Egypt and Russia, since the history of these relations goes back more tha n two centuries, and currently Russia is considered one of the strongest economies in the world, one of the ten strongest economies in the world, according to the latest report from the International Monetary Fund, and is also the strongest economy in the Eurasian Union.Tasks. Analysis of the most important economic projects in various sectors such as the agriculture and food sector, transport, free zones, energy and military cooperation, tourism between Egypt and the Russian Federation in the period from 2014 to the present, determining the degree of effectiveness of these joint projects and factors contributing to increase in the efficiency of the efficiency of the implementation of these projects and increase economic feasibility. Explore cross-culture barriers that hinder the establishment of closer contacts between the private businesses of both sides.Methods. In this work, using the methods of logical and statistical analysis, factors were identified that contribute to the effectiveness of economic and investment interaction used in the implementation of projects aimed at bilateral development at the state level. The problems arising at the level of interaction between the private sectors of the economy of both countries were also noted.Results. The study showed that economic projects between Egypt and the Russian Federation at the governmental level (governments, agencies, companies and public institutions) can still be considered essential for the Egyptian economy in order to achieve sustainable development, to which it aspires, but, on the contrary, for the private sector it is s till unsatisfactory and very small due to a group of intercultural obstacles, which, in our opinion, are not difficult to overcome.Conclusions. It is advisable to consider aspects of cooperation between Egypt and Russia on a wider and more comprehensive scale than at present, and to use the opportunities available at the level of the public sector on a wider scale. With regard to trade cooperation at the private sector level, it is necessary to develop a plan to increase the volume of trade between the two countries, and it would be useful to enlist the support of the government authorities of the EEA countries.